THE SENTENCE AS A UNIT OF SYNTAX IN ENGLISH: STRUCTURE AND TYPES - Nazokat Inoyatulloyeva Izzatullo qizi (TADQIQOTLAR, 2026)
Annotation This paper explores the sentence as a fundamental unit of syntax in English, with a particular focus on the differences between spoken and written sentence structures. The  study  highlights  how  spoken  language  tends  to  be  more  spontaneous,  less structured, and context-dependent, often characterized by ellipsis, coordination, and the use of fillers. In contrast, written language is presented as more formal, organized, and  precise,  relying  on  complex  sentence  constructions,  subordination,  and punctuation for clarity. The paper emphasizes the role of the sentence in conveying meaning, structuring thought, and fulfilling communicative purposes across different modes of language use. It concludes that understanding sentence structure enhances both  linguistic  competence  and  effective  communication,  demonstrating  the importance of syntax in expressing ideas clearly and accurately.